Hijab No More: A Phenomenological Study - Syahrivar, Jhanghiz (Journal of religion and health, 2021)
The consumption of Islamic products has been discussed quite extensively in many studies, yet the opposite case which is the dissociation from Islamic products is rarely discussed. This study aims to investigate the phenomena in which Muslim women who were raised with conservative values at home countries choose to dissociate from hijab when they live in the western countries. Moreover, they become activists who discourage other Muslim women from wearing hijab. This study adopts a phenomenological research design. The results suggest that hijab dissociation is a form of compensatory mechanism aimed at minimizing self-discrepancy, restoring self-esteem, gaining personal control, reducing perceived alienation and coping with psychological trauma. This study contributes to the theoretical gap in compensatory consumption literature by linking the theory with the non-consumption of religious products.